2010
DOI: 10.1186/1476-4598-9-109
|View full text |Cite
|
Sign up to set email alerts
|

The anti-aging gene KLOTHO is a novel target for epigenetic silencing in human cervical carcinoma

Abstract: BackgroundKlotho was originally characterized as an anti-aging gene that predisposed Klotho-deficient mice to a premature aging-like syndrome. Recently, KLOTHO was reported to function as a secreted Wnt antagonist and as a tumor suppressor. Epigenetic gene silencing of secreted Wnt antagonists is considered a common event in a wide range of human malignancies. Abnormal activation of the canonical Wnt pathway due to epigenetic deregulation of Wnt antagonists is thought to play a crucial role in cervical tumorig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
138
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(154 citation statements)
references
References 24 publications
9
138
0
7
Order By: Relevance
“…This possibility is strengthened by recent work indicating that promoter methylation may, in part, explain why expression of KL is restricted to a limited number of organs (Azuma et al 2012). Beyond normal processes, regulation of KL through methylation of its promoter is reported in multiple cancers (Camilli et al 2010;Chen et al 2010;Lee et al 2010;Wolf et al 2008).…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…This possibility is strengthened by recent work indicating that promoter methylation may, in part, explain why expression of KL is restricted to a limited number of organs (Azuma et al 2012). Beyond normal processes, regulation of KL through methylation of its promoter is reported in multiple cancers (Camilli et al 2010;Chen et al 2010;Lee et al 2010;Wolf et al 2008).…”
Section: Introductionmentioning
confidence: 71%
“…KL has also been implicated as a tumor-suppressor protein in numerous cancers (Camilli 2010;Chang et al 2012;Chen 2010;Lee 2010;Wang 2011;Wolf 2008) where decreased expression promotes tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Mice deficient in Klotho expression exhibit increased renal gene expression of STC1 and STC2 compared with wild-type mice (19). Moreover, the level of Klotho was found to be downregulated in breast, lung, colon, pancreatic, gastric and cervical cancer (36)(37)(38). Although evidence suggests that Klotho acts as a tumor suppressor in numerous cancers (39), little is known concerning its potential effect on thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Klotho can inhibit the activation of the Wnt signaling pathway (22). Lee reported that Klotho functioned as a Wnt antagonist in a cervical cancer cell line and that the expression of Klotho in SiHa cells resulted in a decrease in N-cadherin (23). In addition, the IGF-1 signaling pathway has been shown to have a strong influence on the EMT process (14).…”
Section: Discussionmentioning
confidence: 99%